1999
DOI: 10.1002/(sici)1097-4636(199911)47:2<251::aid-jbm16>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cell recruitment, distribution, and chemiluminescence response at IgG precoated- and thiol functionalized gold surfaces

Abstract: The role of complement activation by artificial surfaces relative to inflammatory response is not well understood. This study was performed to evaluate the inflammatory cell recruitment, distribution, and ex vivo metabolic activation of surfaces with different plasma protein adsorption and complement activation properties in vitro. The implants were (1) pure gold (reference), (2) albumin-precoated (3) IgG-precoated gold, and (4) 3-mercapto-1, 2-propanediol [mercaptoglycerol (MG)] and (5) glutathione (GSH) immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This is in correlation with previous in vivo 6 and in vitro 4,5 studies. Ellipsometric data from hydrophobic silicon surfaces showed that the IgG surface concentration was retained at a consistent level for days, but declined within hours on hydrophilic silicon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in correlation with previous in vivo 6 and in vitro 4,5 studies. Ellipsometric data from hydrophobic silicon surfaces showed that the IgG surface concentration was retained at a consistent level for days, but declined within hours on hydrophilic silicon.…”
Section: Discussionsupporting
confidence: 92%
“…3 Albumin is suggested to blunt the inflammatory response 4 and adsorbed IgG is known to activate and recruit blood cells in vitro 4,5 and in vivo. 6 The activation of complement during blood-bio material interactions is a clinically observed phenomenon, [7][8][9][10][11] although the mechanisms are not fully understood. Probably both the classical and the alternative complement pathways are involved.…”
Section: Introductionmentioning
confidence: 99%
“…Tang and Eaton showed that IgG-deficient mice apparently respond with a normal inflammatory reaction after implantation [29], but in another study a very potent in vivo inflammatory reaction was triggered by surface-bound IgG [30]. We have previously demonstrated that platelets amplify the IgG-triggered neutrophil respiratory burst in response to phagocytosable [17] and non-phagocytosable preys [31] in non-stirred systems.…”
Section: Discussionmentioning
confidence: 97%
“…Examples of such products are C3a, C5a, and sC5b‐9; they cause local or systemic inflammatory reactions governed by the site for activation 6. The activated complement cascade can pose a major problem concerning medical implants and extracorporeal blood treatment devices 7, 8. It also seems to have long‐term implications, for example, in‐wear debris from total joint arthroplasty9 and xenotransplantation 10…”
Section: Introductionmentioning
confidence: 99%